Getting close and personal with inmates of RSK Bedong and students of Semuji in a community project ‘Semaian Budi'. - Wan Nazrul Helmy, Wan Mohd Zain
Thirty five Universiti Malaysia Pahang (UMP) undergraduates had a meaningful semester holiday by taking some time off to be with inmates of Rumah Seri Kenangan (RSK) Bedong and students of Sekolah Menengah Sains Sultan Mohamad Jiwa (SEMUJI) in Sungai Petani, Kedah.